In Vitro Gastrointestinal Release of Chlorogenic Acid and Curcumin Co-Encapsulated in Double Emulsions with the Outer Interface Stabilized by Cellulose Nanocrystals - Gimenez-Castillo, B; Paredes-Toledo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A Pickering double emulsion (DE) with an outer (O:W2) interface stabilized by cellulose nanocrystals (DE-CNC) was designed as a co-delivery systems for chlorogenic acid (CA) and curcumin, then compared with a control DE emulsion with an O:W2 interface stabilized with sodium caseinate (DE-NaCas). DE-CNC was more resistant to creaming during storage (6.79%, day 42) and showed higher encapsulation efficiency (EE) of CA (>90%). Conversely, both DEs exhibited similarly high EE for curcumin (>97%). The ζ-potential values were highly negative in both DEs, but tended to be lower in DE-CNC due to the highly negative charge of the CNCs. DE-CNC allowed for a steady release of CA during the oral, gastric, and intestinal phases of digestion, while a total release of CA was already observed in the gastric phase in case of DE-NaCas. The bioaccessibility of CA was similar in both DEs (~57–58%). Curcumin was mainly released in the intestinal phase with both DEs, reaching slightly lower bioaccessibility values with DE-CNC. The use of CNCs as a stabilizer for the outer interface of DEs is a promising strategy to increase the stability and EE of these systems, providing oral co-delivery vehicles capable of releasing significantly bioactive compounds during the intestinal phase of digestion. © 2024 by the authors.